2020
DOI: 10.1111/wrr.12853
|View full text |Cite
|
Sign up to set email alerts
|

Potential markers of healing from near infrared spectroscopy imaging of venous leg ulcer. A randomized controlled clinical trial comparing conventional with hyperbaric oxygen treatment

Abstract: The aim of this study is to ascertain whether the simultaneous measurement of hemoglobin O2 saturation (StO2) and dimension of venous leg ulcers (VLU) by near infrared spectroscopy (NIRS) imaging can predict the healing course with protocols employing a conventional treatment alone or in combination with hyperbaric oxygen therapy (HBOT). NIRS 2D images of wound region were obtained in 81 patients with hard‐to‐heal VLU that had been assigned, in a randomized controlled clinical trial, to the following protocols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Longobardi et al ( 31 ) compared two different regimes of HBOT, namely twice a day for 3 weeks or once daily for 6 weeks, with standard treatment in a group of 81 patients with hard to heal venous ulcers. Healing was defined as a minimum wound area reduction of 40% and was highest in the 6-week HBOT group, and lowest in the 3-week HBOT group.…”
Section: Discussionmentioning
confidence: 99%
“…Longobardi et al ( 31 ) compared two different regimes of HBOT, namely twice a day for 3 weeks or once daily for 6 weeks, with standard treatment in a group of 81 patients with hard to heal venous ulcers. Healing was defined as a minimum wound area reduction of 40% and was highest in the 6-week HBOT group, and lowest in the 3-week HBOT group.…”
Section: Discussionmentioning
confidence: 99%
“…5 studies were identified for inclusion. 11-15 Figure 1 illustrates a flow diagram of this process.
Figure 1.PRISMA flow diagram charting the literature search.
…”
Section: Resultsmentioning
confidence: 99%
“…Longobardi et al reported a reduced healing rate when 2.4 ATA, 66 min, twice a day were used, which is higher pressure and more frequent use of HBOT compared with those of our protocol. 8) This result was possibly related to too much oxygen toxicity. Further pieces of evidence are necessary to elucidate the selection of appropriate candidates and modes of HBOT in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent prospective trials failed to demonstrate the superiority of HBOT in terms of healing rate when compared with placebo or standard treatment. 7 , 8 ) These trials included VLUs that responded poorly to a 4 week standard treatment. By contrast, Bass reported that 15 of 19 VLUs, which had not healed for a median of 10.1 years, healed after a median of 60.7 (10–200) h of HBOT.…”
Section: Discussionmentioning
confidence: 99%